Interactions and management of the Stakeholders-Tourists-Trails-Environment system at Látrabjarg Cliffs (Iceland): a comparative study with Moher Cliffs (Ireland) - Legatelois, Marie Jannie Madeleine, 1989- (2014)
Látrabjarg Cliffs (Iceland) are the biggest cliffs and sea bird colony of Europe. This site attracts an increasing number of international tourists. However, the current infrastructure presents on the site is not adapted for this tourism and the resulting pressure on the environment raises issues for the sustainability of this important site. Stakeholders are currently transforming Látrabjarg into a National Park and developing conservation and land-use plans to address these issues. The research objective is to help this development process by gathering information on how tourism should be managed at Látrabjarg in order to ensure sustainability of this tourist destination. In order to meet this objective, a mixed method approach was chosen. Information was collected through a qualitative comparison with the planning and management process of Moher Cliffs (Ireland) case study. This tourist destination was chosen because of its many environmental and management similarities with Látrabjarg Cliffs. Information was also collected through on-site direct and indirect observations, key stakeholder’s meeting. Literature and information analysis was done to answer research questions. The research has proposed a new approach for tourist destinations study through the Stakeholders-tourists-trails-environment systems (STTES) framework. The research found that the current path of Látrabjarg planning process presents numerous issues and concerns. These included stakeholder’s conflicts and improper involvement, a profound lack of base data and analyses about tourists, society, economy, environment and tourist impacts, general lack of environmental and sustainability considerations and poor planning timeline. Considering these findings, failure in tourism management, the sustainability of the STTES, nature conservation, and sustainability of Látrabjarg National Park is likely. The main recommendations of this research are to conduct more research before going forward in the planning process, to ensure proper and ethical ...